Prevention of excitotoxicity‐induced processing of BDNF receptor TrkB‐FL leads to stroke neuroprotection - Tejeda, Gonzalo S (EMBO Mol Med, 2019)
Neuroprotective strategies aimed to pharmacologically treat stroke, a prominent cause of death, disability, and dementia, have remained elusive. A promising approach is restriction of excitotoxic neuronal death in the infarct penumbra through enhancement of survival pathways initiated by brain‐derived neurotrophic factor (BDNF). However, boosting of neurotrophic signaling after ischemia is challenged by downregulation of BDNF high‐affinity receptor, full‐length tropomyosin‐related kinase B (TrkB‐FL), due to calpain‐degradation, and, secondarily, regulated intramembrane proteolysis. Here, we have designed a blood–brain barrier (BBB) permeable peptide containing TrkB‐FL sequences (TFL(457)) which prevents receptor disappearance from the neuronal surface, early induced after excitotoxicity. In this way, TFL(457) interferes TrkB‐FL cleavage by both proteolytic systems and increases neuronal viability via a PLCγ‐dependent mechanism. By preserving downstream CREB and MEF2 promoter activities, TFL(457) initiates a feedback mechanism favoring increased levels in excitotoxic neurons of critical prosurvival mRNAs and proteins. This neuroprotective peptide could be highly relevant for stroke therapy since, in a mouse ischemia model, it counteracts TrkB‐FL downregulation in the infarcted brain, efficiently decreases infarct size, and improves neurological outcome.